USING PADLET TO INCREASE THE STUDENTS’ PROCEDURE TEXT WRITING ACHIEVEMENT - Dian Fadhilawati; Dwita Laksmita Rachmawati; Moh Mansur (Universitas Muhammadiyah Makassar, 2020)
The purpose of this research was to improve the Students’ procedure text writing achievement at English Conversation Club (ECC) MAN Kota Blitar by applying Padlet. The research design used was classroom action research (CAR) which covered 4 steps; 1) Planning, 2) Acting, 3) Observing and evaluating and 4) Reflecting. The Subjects of this research were 50 students from X Grade who join ECC in MAN Kota Blitar.The data collection methods of this research were taken from administering tests and distributing the questionnaire. The research result proved that the use of Padlet for teaching writing of procedure text could increase the students’ writing achievement of procedure text from preliminary action 57.55 increased to 72.85 in cycle 1. Based on the result of cycle 1, it did not fulfill the minimum criterion mastery 75.00; therefore, the researchers continued the research to cycle 2 and got satisfying result 82.65. Furthermore, the students’ of ECC MAN Kota Blitar also presented positive attitude toward the use of Padlet in teaching and learning writing of procedure text.